Implementasi Model DevOps Pada Pengembangan Sistem Informasi Satuan Pendidikan Nonformal - Nia Umilizah; Azhar Andhika Putra; Feby D. Nursyahidah; Ade Sukma Wati (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2024)
Information system development is one of the important aspects of supporting modern business operations and strategies. In an increasingly dynamic digital era, the need to produce fast, efficient, and reliable systems encourages organizations to adopt new approaches in information system development. SKB Palembang City still uses ledger media, bulletin boards, and Microsoft Office assistance such as Microsoft Word, making it difficult for people and students to get information about schools and learning materials. The research results show that the application of the DevOps Model in the development of information systems can produce an efficient system with a perfect level of usability according to the SUS evaluation. The average score of 82.5 reflects user satisfaction with the system, although some minor aspects require improvement.